2019
DOI: 10.1007/s00167-019-05803-w
|View full text |Cite
|
Sign up to set email alerts
|

Stress radiography at 30° of knee flexion is a reliable evaluation tool for high-grade rotatory laxity in complete ACL-injured knees

Abstract: Purpose To evaluate the diagnostic value of stress radiography and determine the cutoff values for high‐grade anterolateral rotatory laxity in complete anterior cruciate ligament (ACL)‐deficient knees at different positions. Methods Forty‐two patients with complete ACL rupture (group 1) and 37 normal subjects (group 2) were prospectively enrolled. The amount of anterior translation in the medial (MM) and lateral (LL) distance compartments and the difference between them (LL‐MM distance) were measured using str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Stress radiographs were reliable in diagnosing ACL tears, with high sensitivities and specificities. 1,2,5,8,13,14,16,24 Furthermore, this review found 30°of knee flexion optimal for assessing ACL integrity through stress radiography. In addition, standing stress radiography was reliable in diagnosing ACL tears, particularly secondary failures, failures .4 years, and injuries with associated meniscal injuries.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Stress radiographs were reliable in diagnosing ACL tears, with high sensitivities and specificities. 1,2,5,8,13,14,16,24 Furthermore, this review found 30°of knee flexion optimal for assessing ACL integrity through stress radiography. In addition, standing stress radiography was reliable in diagnosing ACL tears, particularly secondary failures, failures .4 years, and injuries with associated meniscal injuries.…”
Section: Discussionmentioning
confidence: 84%
“…1 The Telos device was reported to have a sensitivity ranging from 88% to 95% and a specificity ranging from 80.7% to 96%, compared with the KT-1000 arthrometer, which had a sensitivity of 72.1% and specificity of 91.9%. 6,16 Kim et al 13 1.1 further stratified the sensitivities and specificities of the Telos device by comparing medial and lateral compartment ATT values. They reported that measuring the medial compartment had a sensitivity of 94.6% and a specificity of 81.1% while measuring the lateral compartment had a sensitivity of 94.6% and a specificity of 80.7%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative stress radiographs were obtained using a Telos device (Metax, Hungen, Germany) at 250 N [21, 27]. The side‐to‐side differences between the injured and the contra‐lateral uninjured knees were measured using anatomic points of the medial compartment of the knee [21].…”
Section: Methodsmentioning
confidence: 99%
“…Preoperative stress radiographs were obtained using a Telos device (Metax, Hungen, Germany) at 250 N [21, 27]. The side‐to‐side differences between the injured and the contra‐lateral uninjured knees were measured using anatomic points of the medial compartment of the knee [21]. The mechanical axis alignment was evaluated using standardized full‐length weight‐bearing radiographs, and categorized as positive for valgus alignment and negative for varus alignment (greater or less than 0°).…”
Section: Methodsmentioning
confidence: 99%